Exclusive Breastfeeding Knowledge, Intention to Practice and Predictors among Primiparous Women in Enugu South-East, Nigeria - Chikaodili N. Ihudiebube-Splendor; Chinyelu B. Okafor; Agnes N. Anarado; Nonyelum N. Jisieike-Onuigbo; Anthonia U. Chinweuba; Ada C. Nwaneri; Joyce C. Arinze; Paulina C. Chikeme (Journal of Pregnancy)
Breastfeeding is considered as the most complete nutritional source for infants because breast milk contains the essential carbohydrates, fats, proteins, and immunological factors needed for infants to thrive and resist infection in the formative first year of life. Knowledge of exclusive breastfeeding (EBF) among women is essential when promoting optimal breastfeeding practices. This cross-sectional descriptive survey assessed knowledge and intention to practice EBF and its associated factors during pregnancy among primiparous women in selected communities in Enugu State, Nigeria. A total population study that applied inclusion criteria was used to recruit 201 primiparous mothers attending their third trimester antenatal care from selected health facilities in rural and urban communities in Enugu State. A researcher-developed questionnaire was used to collect data on participants’ knowledge and intention to practice EBF. Descriptive statistics of frequency, percentage, mean, and standard deviation were used to summarize categorical and continuous variables while Chi-square and Wald statistic tests predicted demographic data associated with knowledge status and intention to practice EBF of the participants. More than half (58.7%) of primiparous mothers had inadequate knowledge of EBF and only 62.7% had intention to exclusively breastfeed for 4–6 months. The Chi-square test result showed significant difference in the participants’ place of residence (p = 0.024), EBF knowledge sources (p = 0.001), and EBF knowledge. The Wald statistic in Logistic regression model indicated the coefficient of age (p = 0.026), educational attainment (p = 0.046), EBF knowledge (p = 0.016), and sources of information about EBF (p = 0.027) to be significant predictors of good intention to practise EBF. Poor EBF knowledge and intention to practice in this population may be improved by combining facility-based and in-house methods of breastfeeding counseling, education, and support especially to intending and expectant mothers. Further studies are needed to be done using the multiparous women as well as assessing the effects of in-house EBF supportive-educative intervention to improve breastfeeding outcomes.